2010
DOI: 10.1038/emboj.2010.335
|View full text |Cite
|
Sign up to set email alerts
|

Asf1b, the necessary Asf1 isoform for proliferation, is predictive of outcome in breast cancer

Abstract: Mammalian cells possess two isoforms of the histone H3–H4 chaperone anti‐silencing function 1 (Asf1), Asf1a and Asf1b. However to date, whether they have individual physiological roles has remained elusive. Here, we aim to elucidate the functional importance of Asf1 isoforms concerning both basic and applied aspects. First, we reveal a specific proliferation‐dependent expression of human Asf1b unparalleled by Asf1a. Strikingly, in cultured cells, both mRNA and protein corresponding to Asf1b decrease upon cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
163
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(180 citation statements)
references
References 62 publications
12
163
0
Order By: Relevance
“…Moreover, breast cancer patients with high expression of Asf1b had a poorer prognosis and higher level of metastasis. 42 Interestingly, Asf1b is one of the proteins involved in the activity of bortezomib, although its precise function requires further validation. 43 Taken together, these results indicate that miR-214 interferes in the replication process of myeloma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, breast cancer patients with high expression of Asf1b had a poorer prognosis and higher level of metastasis. 42 Interestingly, Asf1b is one of the proteins involved in the activity of bortezomib, although its precise function requires further validation. 43 Taken together, these results indicate that miR-214 interferes in the replication process of myeloma cells.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease of Asf1b has been described in various types of quiescent human cells. 42 Asf1b is a specific marker for discriminating between cycling and noncycling cells and is a marker of proliferation status in breast cancer. Tumor cells transfected with siRNA against Asf1b decreased the ability to form colonies.…”
Section: Discussionmentioning
confidence: 99%
“…31 We previously demonstrated that islet expression of Asf1b strongly correlated with the susceptibility of 2 mouse strains to obesity-induced diabetes 36 and with b-cell proliferation, consistent with studies in cancer showing that ASF1B plays a major role in cellular proliferation. 49 Our RNA-sequencing of human islets and gene ontology analysis highlighted changes in gene regulation that supported a role for ASF1B in b-cell proliferation. ASF1B overexpression induced several genes involved in cell cycle regulation (see Table S3), including genes that mediate the G 1 /S transition, M phase, chromatin regulators, and cellular morphogenesis/organization.…”
Section: Discussionmentioning
confidence: 99%
“…43,49,61 Initially, ASF1 proteins were implicated in the formation of replication-coupling assembly factor (RCAF). 62 However, more recent reports show that ASF1B can directly interact with the B-domain of HIRA, suggesting that it may play a role in RI histone deposition.…”
Section: Discussionmentioning
confidence: 99%
“…In yeast, the absence of ASF1 leads to enhanced genetic instability and sister chromatid exchange (Prado et al, 2004). Recent study revealed that the expression of ASF1B, like CAF-1A, was proliferation-dependent (Corpet et al, 2011 Our initial results demonstrated that the MOZ portion of the MOZ-TIF2 fusion protein interacted with the human CAF-1A and ASF1B. These associations are consistent with previous findings that a MYST family member in yeast, SAS (something about silencing) protein, interacts with Cac1, a yeast homologue of human CAF-1A, and yeast ASF1 and that the interaction contributed to the silencing of the ribosomal DNA locus (Meijsing and Ehrenhofer-Murray, 2001).…”
Section: Discussionmentioning
confidence: 99%